Plum Pox Virus and Sharka Disease - Garcia, Juan Antonio; Cambra, Mariano (Global Science Books (GSB), 2020)
Sharka is a disease of fruiting, ornamental and wild Prunus species of great socio-economic relevance that has spread to most Prunus- growing nations. It is caused by Plum pox virus (PPV), a member of the genus Potyvirus. In recent years, there have been notable advances in our understanding of genome organization and expression, functions of gene products, and pathogenicity and host range determinants of PPV and other potyviruses. This knowledge is being applied to improve PPV detection and strain differentiation. In addition, the feasibility of engineering the PPV genome through cDNA cloning has opened the possibility of using PPV as a biotechnological tool. The combined application of classical breeding and genetic engineering techniques is yielding first results in the development of Prunus cultivars resistant to sharka disease.